“COMPARATIVE MORPHOMETRIC ANALYSIS OF THE RIVER BASINS OF THE NIRA, KARHA, AND BHIMA IN BARAMATI TEHSIL, MAHARASHTRA” (CAHIERS MAGELLANES-NS, 2024)
The research on comparative morphometric analysis of the river basins of the Nira, Bhima, and Karha, situated in the Baramati Tehsil, Pune District, Maharashtra, India, is discussed in this paper. The basins that originate from the Sahyadri highlands in western Maharashtra are the subject of this study. It uses 1:50,000 scale topographic maps from the Survey of India (SOI) and 30-meter spatial resolution data from the SRTM-DEM.ArcGIS 10.4 is used for analysis; in particular, tools like Surface and Arc Hydro are used. The goal of the study is to measure morphometric parameters, such as the slopes of the basins under analysis, stream orders, and watershed boundaries.These basins rivers are classified as 5th to 7th order streams, according to the analysis. It is determined that there are 1603, 2543, and 750 streams in the Nira, Karha, and Bhima basins, respectively, with total lengths of 1071.98 km, 1892.83 km, and 535.36 km. When comparing the Karha river basin to the Nira and Bhima basins, comparative analyses of areal, linear, and relief parameters reveal that the Karha river basin has more developed features. Every basin has a dendritic drainage pattern, with the Karha basin being longer and undergoing significant processes related to erosion. This study emphasizes how crucial it is to comprehend these river basins' hydrologic behaviours and geomorphological and hydro-geological features in order to manage them effectively and preserve natural resources in a sustainable manner. The results highlight the critical need for targeted development plans in the Karha basin in order to protect regional environmental sustainability and sustain local livelihoods.